Key data on vocational training in the European Union - (:unkn) unknown (Office for Official Publications of the European Communities, 1997)
The present report has been produced in response to the growing awareness of the important role to be played by vocational education and training in helping to improve competitiveness of the EU and its Member States, and to promote international cohesion within the Union. It is devided into five chapters: Chapter A looks at the demographic and labour market situation to which developments in vocational education and training are having to respond. Chapter B provides a statistical description of the initial vocational training programmes in place in each of the Member States. The continuing vocational training provided by enterprises for their employees is the subject of chapter C. Chapter D compares the training experiences of the self-employed to those of employees by Member state. Finally, Chapter E presents information on the European Community programmes and initiatives financed through the European Social Fund (ESF) and the Leonardo da Vinci Programme. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 1.2.3.1 Potenziale; S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.2 Europa; Berufsbildung; Bildungsniveau; Demografischer Wandel; Arbeitsmarkt; Berufsausbildung; Betriebliche Weiterbildung; Berufsbildungsstatistik; EU-Programm; Europäische Union